2020
DOI: 10.3389/fonc.2020.00112
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Thyroid Nodules Difficult to Diagnose With Contrast-Enhanced Ultrasonography and Real-Time Elastography

Abstract: According to the 2015 American Thyroid Association (ATA), referred risk stratification and thyroid nodules with intermediate-and low-suspicion patterns are difficult to diagnose. The objective of this study is to evaluate the diagnostic performance of contrast-enhanced ultrasonography (CEUS) and elastosonography (ES) for the differentiation of these thyroid nodules. From November 2011 to June 2016, a total of 163 thyroid nodules with intermediate-and low-suspicion patterns in 150 consecutive patients at our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
2
15
0
2
Order By: Relevance
“…CEUS enhancement provides additional significant patterns for differentiating benign and malignant nodules with intermediate and low suspicion (5-20% malignancy risk). This risk can increase to 38.5% if the nodule shows heterogeneous enhancement [109]. With nodular goiter and subacute thyroiditis, a visible peripheral enhancement may be observed, as they are hyperplastic or atrophic in architecture.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS enhancement provides additional significant patterns for differentiating benign and malignant nodules with intermediate and low suspicion (5-20% malignancy risk). This risk can increase to 38.5% if the nodule shows heterogeneous enhancement [109]. With nodular goiter and subacute thyroiditis, a visible peripheral enhancement may be observed, as they are hyperplastic or atrophic in architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have also reported prediction models for differentiating benign and malignant thyroid nodules ( 22 , 42 , 48 50 ). However, few of them weighted for the risk factors and it was inconvenient to calculate the risk of malignancy clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Graceffa et al [29] expounded the frequent coexistence of PTC and HT. Similarly, the probability of PTL in HT populations was approximately 50 times higher than the general population [1,9]. This situation highlights the importance of monitoring HT patients, particularly if they have long-lasting disease with nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Elastic image was scored (1-5 points) using colors displayed in the ROI. When elastography points were > 3, hard nodules were indicated [9]. When lymph nodes were roundly enlarged, the hyperechoic structure of the lymphatic hilum disappeared, the internal echo was uneven, and irregular blood ow signals were seen inside, abnormally enlarged lymph nodes were recorded [10].…”
Section: Imaging Analysismentioning
confidence: 99%